PROBLEM DAN TANTANGAN PENGEMBANGAN INOVASI MADRASAH BERBASIS PESANTREN - Oktaviani, Melly; Neneng Hilda Handaniah; Selamet (As-Sulthan Journal of Education, 2025)
This study aims to analyze the issues and challenges faced by pesantren-based madrasahs in implementing management and educational policies for their students. The methodology employed is a literature review, examining various reliable sources related to the administration of madrasahs and pesantren. The findings reveal that the myriad challenges and problems confronting pesantren-based madrasahs arise not only from external factors but also from numerous internal issues, such as limited human resources, suboptimal management practices, and a curriculum that has not yet fully adapted to contemporary needs. Inadequate facilities and infrastructure further impede the innovative processes. Based on these findings, the research concludes that there is a pressing need to enhance the quality of human resources through training and professional development, improve educational management, revise and develop a more contextual and integrative curriculum, as well as procure and upgrade the facilities that support the learning process. It is anticipated that these efforts will strengthen pesantren-based madrasahs as adaptive and innovative educational institutions capable of navigating the dynamics of modern educational developments while preserving the Islamic values that are their hallmark.